Aplikasi Greenship Interior Space versi 1.0 pada Perancangan Interior Panderman Hill Resort Hotel - Purnama Esa Dora, Melina Sugiarti S.P. Honggowidjaja (Intra, 2014)
The development of tourism in Batu, Indonesia began to grow rapidly. This condition shows that there is an increasing number of people needs traveled in the area adjacent to nature. To facilitate what tourism needs, so we made a Green Interior Resort Hotel that can facilitate stay overnights with the excellence of the green interior concept application which is expected to become a new tourist destination icon.                The data analysis done with literature study, the data retrieval with comparative study and fields survey directly. While designing done with programmatic approach that involve programming, schematic design, and technical drawing.                The aim of this design is to produce a design that applies various variables of Greenship Interior Space versi 1.0 and get platinum certification level.